2022
DOI: 10.3233/ch-211367
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of contrast-enhanced ultrasound and superb microvascular imaging in differentiating benign from malignant solid breast lesions: A systematic review and meta-analysis

Abstract: OBJECTIVE: To investigate the added value of contrast-enhanced ultrasound (CEUS) and superb microvascular imaging (SMI) to the conventional ultrasound (US) in the diagnosis of breast lesions. METHODS: PubMed, EMBASE, Web of Science, Chinese national knowledge infrastructure databases, Chinese biomedical literature databases, and Wanfang were searched for relevant studies from November 2015 to November 2021. The quality of the included studies was evaluated using the Quality Assessment of Diagnostic Studies (QU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The growth rate of tumors is slow during the slow growth stage, but in the rapid proliferation stage, tumors grow fast after rich microangiogenesis which promotes rapid growth of tumors ( 19 ). Therefore, the evaluation of microangiogenesis in breast lesions is important to differentiate malignant from benign lesions ( 20 ). The characteristics of neovascularization in malignant breast nodules usually include large quantity, thin wall, disorganized tortuosity, and formation of arteriovenous fistula ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The growth rate of tumors is slow during the slow growth stage, but in the rapid proliferation stage, tumors grow fast after rich microangiogenesis which promotes rapid growth of tumors ( 19 ). Therefore, the evaluation of microangiogenesis in breast lesions is important to differentiate malignant from benign lesions ( 20 ). The characteristics of neovascularization in malignant breast nodules usually include large quantity, thin wall, disorganized tortuosity, and formation of arteriovenous fistula ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are hundreds of studies, including papers, reviews, and meta-analyses dealing with the application of CEUS in the diagnosis of breast tumors in women, which is one of the most diffuse oncological pathologies worldwide [92][93][94][95][96][97][98][99][100].…”
Section: Ceus In Mammary Gland Tumorsmentioning
confidence: 99%
“…Thus, CEUS proved to be ineffective in the differentiation of canine mammary tumors, although it was very useful in identifying neoplastic macro and micro vascularization [44]. Conversely, recent systematic reviews and meta-analysis in women showed that CEUS is a good tool for improving ultrasound in differentiating benign and malignant breast lesions [100,105], as well as predicting pathological response in patients with breast cancer and NAC [95].…”
Section: Ceus In Mammary Gland Tumorsmentioning
confidence: 99%
“…Superb microvascular imaging (SMI) uses an adaptive algorithm to analyze the characteristics of motion artifacts, eliminate clutter signals, and realize low-speed microvascular visualization at a higher frame rate, higher spatial resolution, and with fewer motion artifacts without injecting contrast enhancement media [ 20 ]. SMI can operate in color SMI (cSMI) and monochrome SMI (mSMI).…”
Section: Introductionmentioning
confidence: 99%